Elucidation of Public Welfare and Social Security Policies in Facing Global Challenges - Reza Kiani (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The welfare and social security system in our time, due to the developments and global conditions, has faced various crises and challenges. For this reason, recognizing the crises and harms of the social security system and adopting policies to deal with those crises are among the important issues in social welfare research. Having a favorable level of social welfare for citizens is considered to be one of the characteristics of a developed society and the result of extensive developments in the development system of countries because this issue plays an important role in the state of benefiting from welfare services and economic security of the entire society. One of the most important scientific sources for understanding the state of social security systems is the reports prepared, compiled and published by the International Union of Social Security. Recently, in a book entitled "Ten Global Challenges of Social Security", this organization has explored and examined the challenges of the social security system on a macro level and proposed policies to deal with that challenge. In this article, in line with this report, the concepts, policies, indicators and criteria mentioned in this important book have been examined and the challenges facing the country's social security system have been presented and examined.